An unfinished struggle?: the guerrilla experience and the shaping of political culture in the Cuban revolution - Clayfield, Anna (2013)
In the years that immediately followed the victory of the rebel forces in 1959, the new leaders of the Cuban Revolution seemed to approach the task of revolutionary governance as a continuation of the guerrilla campaign in the sierra. The leadership's empirical management of the Revolution in power betrayed its guerrilla roots, and resulted in an inchoate political system headed by charismatic guerrilleros. By the end of the first decade, however, it seemed that the Revolution's guerrilla past had been all but forgotten, as it established closer ties with the Soviet Union and subsequently underwent a process of 'institutionalisation'. Since that time, many Western scholars of Cuba have commented on the increased role of the military in the revolutionary leadership, and in other aspects of the Revolution which would normally be considered to be beyond the remit of most armed forces. These scholars have concluded that the pervasive presence of the military is evidence of the 'militarisation' of the Cuban Revolution.